2009
DOI: 10.1007/s10482-009-9395-7
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation and injury of Escherichia coli in a copper water storage vessel: effects of temperature and pH

Abstract: Copper has been used as a disinfectant since ancient times and recent research has demonstrated that antimicrobial copper surfaces may have practical applications in healthcare and related areas. The present study was carried out to establish the effects of temperature and pH on inactivation and sub-lethal injury of Escherichia coli in water stored in a copper vessel, to determine the operational limits of the process in terms of these variables. To investigate the effects of temperature, a bacterial suspensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…This isolate was also used in our previous study (Sharan et al 2010), ensuring comparability with this research. The isolate was preserved by preparation of stocks following sub-culture on nutrient agar (HiMedia, Mumbai, India) at 37°C.…”
Section: Bacterial Culturementioning
confidence: 99%
See 3 more Smart Citations
“…This isolate was also used in our previous study (Sharan et al 2010), ensuring comparability with this research. The isolate was preserved by preparation of stocks following sub-culture on nutrient agar (HiMedia, Mumbai, India) at 37°C.…”
Section: Bacterial Culturementioning
confidence: 99%
“…Copper vessels (capacity 12 l) were obtained from local merchants in Chandigarh, as before (Sharan et al 2010). Each vessel was filled with 10 l of bacterial suspension.…”
Section: Water Source and Storage Vesselsmentioning
confidence: 99%
See 2 more Smart Citations
“…Copper pot is as active in regular drinking-water (pH 7.83±0.4) as that reported by us earlier (12) in distilled water (pH 6.7±0.05), and the level of copper leached in the former is far less (177±16 ppb) than that in distilled water (~420 ppb). Other studies have shown that copper vessel is lethal to E. coli in water at different pH and temperature conditions, with the fastest inactivation occurring as the pH shifts away from neutrality and 35 °C (15). Copper has also been shown to act, to a greater or lesser extent, on E. coli in the presence of organic and inorganic constituents in water (16).…”
Section: Discussionmentioning
confidence: 99%